Exploring tourism perceptions of children through drawing. Issue 3 (3rd July 2021) - Ertaş, Çağdaş; Ghasemi, Vahid; Kuhzady, Salar
ABSTRACT: Understanding perceptions of children has been attracted less attention. Issues related to data collection were noted as the main reason behind less giving voice to children in tourism studies. To fill this gap, the current study aimed to explore the tourism perceptions of children through an innovative method. A group of 30 children has been involved in the aim of this research in Şırnak, Turkey. Data were collected by drawing and open-ended questions. Results indicate that children's perceptions of tourism are significantly positive. Findings also show that such perceptions are listed in three categories: namely, economic, socio-cultural, and environmental. The study discusses the findings through the antecedents of resident attitudes and also suggests directions for future research.